Echocardiographic assessment of the relationship between cardiac function and plasma homocysteine levels in patients with heart failure and preserved ejection fraction - Xie, Zi-Qi; Xie, Qing; Zheng, Xiao-Ye; Wu, Xiao-Juan; Liu, Wei-Hua; Li, Ru; Zhu, Hong-Yan; Zhou, Qi (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHeart failure with preserved ejection fraction (HFpEF) is characterized by normal ejection fraction and diastolic dysfunction. The role of plasma homocysteine (Hcy) levels in HFpEF has been understudied, though elevated levels are known to affect cardiovascular health.MethodsThis retrospective observational study analyzed 80 HFpEF patients and 80 matched controls without HFpEF. Fasting plasma Hcy levels were measured using a dual-antibody sandwich enzyme-linked immunosorbent assay (ELISA). Standard echocardiographic evaluations were performed to measure interventricular septal thickness (IVST), left ventricular posterior wall thickness (LVPWT), left atrial diameter (LAD), left ventricular end-diastolic diameter (LVEDD), left ventricular ejection fraction (LVEF), and the early-to-late diastolic mitral inflow velocity ratio (E/A). Statistical analyses included independent sample t-tests, chi-square tests, Pearson's correlation, and Spearman's rank correlation.ResultsHFpEF patients exhibited significantly higher plasma Hcy levels (45.17 µmol/L) compared with controls (33.85 µmol/L, p < 0.001). Although LVEDD and LVEF did not differ significantly between groups, HFpEF patients demonstrated increased IVST, LVPWT, LAD, and a higher E/A ratio (p < 0.01 for all). Plasma Hcy levels were inversely correlated with LVEF (r = –0.375, p = 0.012) and positively correlated with IVST (r = 0.53), LVPWT (r = 0.45), LAD (r = 0.43), and E/A ratio (r = 0.56; p < 0.01 for each). A strong positive correlation was also observed between Hcy levels and New York Heart Association (NYHA) classification (r = 0.824, p < 0.001).ConclusionsThe findings indicate that elevated plasma homocysteine is associated with myocardial remodeling and impaired diastolic function in HFpEF patients. These results support the potential role of homocysteine as a biomarker for HFpEF severity and progression, warranting further investigation into its utility for risk stratification and targeted therapy.